2012
DOI: 10.1007/s11258-012-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

Micro-evolutionary patterns of juvenile wood density in a pine species

Abstract: Wood density can be considered an adaptive trait, because it ensures the safe and efficient transport of water from the roots to the leaves, mechanical support for the body of the plant and the storage of biological chemicals. Its variability has been extensively described in narrow genetic backgrounds and in wide ranges of forest tree species, but little is known about the extent of natural genetic and phenotypic variability within species. This information is essential to our understanding of the evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
0
17
0
1
Order By: Relevance
“…Southern hemisphere conifers are known for their small tracheids (Pittermann et al , ) that are associated with slow growth rates and denser wood, which may also enhance their resistance to microbial decomposition in rainy environments (Boddy, ). Experimental nutrient additions reduced wood density and increased vulnerability to stem embolism in hybrid poplar saplings (Hacke et al , ), but other studies have shown that reduced wood density in response to increased nutrient availability does not necessarily lead to higher vulnerability (Bucci et al , ; Lamy et al , ; Goldstein et al , ). Future work should quantify embolism resistance in other more cavitation‐prone organs (leaves and roots) to determine whether these can shed additional light on these curious conifers.…”
Section: Discussionmentioning
confidence: 98%
“…Southern hemisphere conifers are known for their small tracheids (Pittermann et al , ) that are associated with slow growth rates and denser wood, which may also enhance their resistance to microbial decomposition in rainy environments (Boddy, ). Experimental nutrient additions reduced wood density and increased vulnerability to stem embolism in hybrid poplar saplings (Hacke et al , ), but other studies have shown that reduced wood density in response to increased nutrient availability does not necessarily lead to higher vulnerability (Bucci et al , ; Lamy et al , ; Goldstein et al , ). Future work should quantify embolism resistance in other more cavitation‐prone organs (leaves and roots) to determine whether these can shed additional light on these curious conifers.…”
Section: Discussionmentioning
confidence: 98%
“…In a series of studies, Lamy et al. (), Lamy, Lagane, Plomion, Cochard, and Delzon (), Lamy et al. () found weak population divergence and significantly lower Q ST than F ST in Pinus pinaster for cavitation resistance and wood density, traits that are also associated with plant hydraulic conductance.…”
Section: Discussionmentioning
confidence: 99%
“…1), Maritime pine has a fragmented distribution, with numerous relatively small and isolated populations (Bucci et al 2007). Reduced gene flow among populations has favored a strong differentiation between them, which is well documented in terms of genetic (González-Martínez et al 2002;Burban and Petit 2003) and phenotypic variation of different adaptive traits (Chambel et al 2007;Corcuera et al 2012;Santos del Blanco et al 2012), other relevant traits for timber production (de la Mata and Zas 2010a; Lamy et al 2012), and herbivore and pathogen resistance (Arrabal et al 2005). For example, intraspecific variation in resin flux (Tadesse et al 2001 Trees polyphenols and condensed tannins in stems and needles , and resin terpene profiles (Arrabal et al 2005;Sampedro et al 2010) have all been reported.…”
mentioning
confidence: 99%